The Effect of Transformational Leadership Values on Worker Performance - Sidik, M. Sayid Nugraha; Desywan, Eko; Raharjo, Susilo Toto; Pradana, Mirwan Surya (LifeSciFi, 2024)
This study examines the impact of transformational leadership values on employee performance, specifically focusing on Relationship Managers (RMs) and RM KPPs within the Yogyakarta Regional Office. Amid the post-COVID economic recovery, banking lending performance in the consumer sector, particularly in property financing, has shown promising growth. This is evidenced by increasing demand for commercial and FLPP property loans, supported by government policies such as tax incentives and FLPP housing procurement initiatives. Despite this potential, challenges remain, including suboptimal achievements in key performance indicators such as outstanding mortgage realization (93.01%) and unmet targets for Special Attention and Non-Performing Loan (NPL) reductions as of October 2024. The study explores how transformational leadership values—such as inspiration, motivation, potential development, and empowerment—impact RMs’ productivity and efficiency in achieving consumer credit targets. Employing a mixed-method approach, the research combines surveys and interviews with RMs in the Yogyakarta Regional Office, using instruments to assess perceptions of leadership styles and their influence on performance. Findings are expected to provide actionable insights for developing leadership training programs aimed at optimizing team performance. Additionally, the study offers strategic recommendations for the banking sector to enhance leadership effectiveness, driving consumer credit growth and improving overall productivity in the Yogyakarta Regional Office.